Unique microswitches positioned extracellular to the orthosteric binding site initiate activation in the β1-adrenergic receptor - Koulgi, Shruti; Harman, Thomas H.; Jones, Andrew J. Y.; Sonavane, Uddhavesh; Nietlispach, Daniel; Sengupta, Durba; Joshi, Manali (Journal of Chemical Information and Modeling, 2026)
Class A GPCRs are known to bind an astonishingly diverse set of agonists, ranging from ions and small molecules to peptides and large proteins that activate these receptors. Interestingly, despite this diversity, agonist binding is described to trigger a conserved activation pathway that propagates changes from beneath the orthosteric agonist-binding site toward the intracellular G protein-coupling site. This suggests the presence of receptor-specific residues upstream of the orthosteric agonist-binding site that not only enable recognition of the ligand but also trigger the common activation mechanism. Using the prototypical beta 1AR-G protein system, we employed microsecond time-scale atomistic molecular dynamics simulations together with NMR experiments to investigate how receptor-specific residues, in conjunction with agonist binding, initiate the conserved activation pathway. We identified state-dependent electrostatic and hydrophobic switches involving unique beta 1AR residues located above the orthosteric binding site, potentially linking them to receptor activation. Our simulations recapitulated the known common activation pathway and also uncovered beta 1AR-specific novel contacts. Additionally, we identified a unique water-mediated R-Y-Y switch near the intracellular end that could facilitate G protein coupling. Overall, based on our work, we propose how evolutionary variations in the extended ligand-binding site could enable receptor-specific agonist recognition, triggering and converging on the common activation mechanism and preserving G protein coupling fidelity.